Understanding the Space-Charge Layer in SnO2 for Enhanced Electron Extraction in Hybrid Perovskite Solar Cells - Sarah Su-O Youn; Kim, Jihyun; Na, Junhong; Jo, William; Kim, Gee Yeong (American Chemical Society, 2022)
Tin oxide (SnO2) has been widely used as an n-type metal oxide electron transport layer in perovskite solar cells (PSCs) owing to its superior electrical and optical properties and low-temperature synthesis process. In particular, the interfacial effect between indium tin oxide (ITO) and SnO2 is an important parameter that controls the charge transport properties and device performance of the PSCs. Therefore, understanding the interfacial effect of ITO/SnO2 and its role in PSCs is crucial, but it is not studied intensively. Herein, we investigated the space-charge effect at the interface of ITO/SnO2 using transfer length measurement and conductive atomic force microscopy as a function of SnO2 thickness. Moreover, optical, morphologic, and device measurements were performed to determine the optimal SnO2 thickness for PSCs. The space-charge effect was identified in ITO/SnO2 when the SnO2 layer was very thin due to electron depletion near the interface. Interestingly, a critical kink point was observed at approximately 10 nm SnO2 thickness, indicating the electron depletion and weak charge transfer behavior of the device. Thus, a thickness around 20 nm was favorable for the best PSC performance because charge transport behavior in the thin SnO2 layer was depressed by electron depletion. However, when the thickness of SnO2 exceeded 50 nm, the device performance deteriorated due to increased series resistance. This study provides a strategy to tune the electron transport layer and boost the charge transport behavior in PSCs, making important contributions to optimizing SnO2-based PSCs.